Stewardship Governance-Based Accountability in the Preparation of Unit Price Standards in Bojonegoro Regency - Rahayu, Dian Puji; Septian, Esa; Junadi, Junadi (The Innovation of Social Studies Journal, 2026)
This study aims to analyze stewardship-based accountability in the preparation of the Unit Price Standard (SSH) in Bojonegoro Regency, emphasizing four primary indicators: trust, commitment, collectivity, and responsibility. The research uses a descriptive, qualitative approach through in-depth interviews, observations of the Desk forum, and scrutiny of documents such as the SSH preparation SOP and SSH data for Fiscal Year 2025. The results show that stewardship principles have begun to be integrated into the SSH preparation process, although their practical implementation is not yet fully optimal. Trust is reflected in the transparency of information and honesty of employees, but is still limited by the inconsistent data quality of OPDs. Commitment is evident in officials' readiness to work beyond regular hours and their quick response to revisions, but is hampered by substantial workloads and tight deadlines. Collectivity emerges in cross-OPD teamwork in the Desk forum, although not all OPDs present comprehensive supporting evidence. Procedural accountability appears strong through the existence of SOP and official SSH documents, while substantive accountability is strengthened through Inspectorate supervision and data correction mechanisms. In conclusion, stewardship governance has provided a positive direction toward a more transparent and responsible work culture. However, it still requires strengthening the data system, increasing technical capacity, and shortening the preparation timeline.